Talking God in society: multidisciplinary (re)constructions of ancient (con)texts : Festschrift for Peter Lampe - Eisen, Ute E.; Mader, Heidrun E.; Daume-Wolff, Mirjam; Ess, Kathleen; Richter, Laura; Wieczorek, Kaja (Vandenhoeck & Ruprecht, 2020)
Peter Lampe#s work has covered a wide range of fields, the common denominator being his interest in contextualizing belief systems. Mirroring his multifaced work, the authors pursue his interest from different interdisciplinary angles, addressing the interdependence between religious expressions and their situations or contexts. The application of theoretical models to texts examples flanks the inspiring theoretical - epistemological and methodological - reflections. Studies in socio-economic and political history adjoin archaeological, epigraphic, papyrological and iconographic investigations. (Social-)psychological interpretations of texts complement rhetorical analyses. The hermeneutical reception of biblical materials in, for example, the Koran and Christian Chinese or Orthodox contexts, as well as in religious education and homiletics, rounds off the volumes
Keywords: Festschrift; Frühchristentum